2009
DOI: 10.1158/0008-5472.can-09-2693
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Novel, Recombinant Immunotoxins Targeting the Her2/neu Oncogene Product: In vitro and In vivo Studies

Abstract: The goal of this study was to characterize a series of antiHer2/neu immunotoxin constructs to identify how different antibodies and linker choices affect the specificity and cytotoxicity of these proteins. We constructed a series of immunotoxins containing either the human single-chain antibody (scFv) C6.5 or the murine scFv e23 fused to the highly toxic recombinant gelonin (rGel) molecule. Based on the flexible GGGGS linker (L), the fusion construct C6.5-L-rGel was compared with e23-L-rGel to evaluate the spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…However, the autophage marker LC3-II had no changes ( Figure 6C). Subsequently, to assess whether the necrotic cell death was induced, we examined lactate LDH release, which is a marker of abrupt membrane lysis [46].The results showed that pCMV-Gel or pSur-Gel significantly increaseed the LDH release in HepG2 cells, and pCMV-Gel also significantly increased the LDH release in LO2 cells, but low in LO2 cells treated with pSurGel ( Figure 6C), which indicated that the observed cytotoxicity may be also a result of necrosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the autophage marker LC3-II had no changes ( Figure 6C). Subsequently, to assess whether the necrotic cell death was induced, we examined lactate LDH release, which is a marker of abrupt membrane lysis [46].The results showed that pCMV-Gel or pSur-Gel significantly increaseed the LDH release in HepG2 cells, and pCMV-Gel also significantly increased the LDH release in LO2 cells, but low in LO2 cells treated with pSurGel ( Figure 6C), which indicated that the observed cytotoxicity may be also a result of necrosis.…”
Section: Discussionmentioning
confidence: 95%
“…Although gelonin toxins have been used to treat malignant cancers many years, studies using different cell types have shown distinct mechanisms underlying the induction of cell death [45][46][47]. Also the mechanism of targeted gelonin gene therapy has no detailed reports.…”
Section: Discussionmentioning
confidence: 99%
“…The immunotoxins were expressed in Escherichia coli strain AD494 (DE3) pLysS and purified by immobilized metal affinity chromatography (IMAC) essentially as previously described (16).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Rabbit anti-rGel antibody and horseradish peroxidase-conjugated goat anti-rabbit IgG were used as a tracer in this assay as described previously (16).…”
Section: Binding Affinity Of Immunotoxinsmentioning
confidence: 99%
See 1 more Smart Citation